’Akkad ’am Bāb ’Ayā - Rašīd, Fauzī
Akkad (i.e. Aggade) or "Gate of Ea"?; ersch. 1987; tablets from Tell Far??d (15 km E by NE of Babylon), excavation nos. 16, 19-27, 29-31, 33-35, 40, 41 ’alif, 41 bā’, 41 ǧīm, dating from the transitional period between the late Ur III and the early OB pe